Schitt's Creek Season 3. - Levy, Eugene; Levy, Dan.; O'Hara, Catherine (United States eOne Label, 2017)
The Rose family is slowly accepting they may never return to their former life of luxury, though Johnny continues to seek new business opportunities in hopes of being wealthy once again.
04/11/2017.
Director, Jerry Ciccoritti, Paul Fox.
Eugene Levy, Dan Levy, Catherine O'Hara.
English audio.
Closed-captioned.
113733
Keywords: Television Series; Comedy Series; Rich People; Poverty